‘FAKE NEWS’ IN ASEAN: LEGISLATIVE RESPONSES - Robert Brian Smith; Mark Perry; Nucharee Nuchkoom Smith (JAS (Journal of ASEAN Studies), 2021)
The research is a legal review based on the documentary research concept by comparing the development of legislative responses to fake news spread in Southeast Asia. Anti-fake news legislation focuses on the transmission of information by electronic means than print media. The analysis is carried out for each of the member states by including a clause-by-clause examination of the legislation and subsequent cases addressing legal issues associated with the laws. Several common factors should be addressed to provide a fairer and more transparent approach, including developing a clear-cut definition of fake news. Two key elements should be met in the definition of spreading of fake news: it should be the intentional spreading of misinformation or disinformation by design. The research suggests it would be better to develop anti-fake news legislation as either a standalone statute or a specific amendment to existing legislation than include fake news in omnibus legislation. Except in the most serious cases, creating, publishing, or distributing fake news illegality should be reduced from a criminal offence to an administrative offence, where the police issue a fine. Given the documented publishing and spreading of disinformation by state actors, their servants and agents, there should be an explicit “fake news” offence associated with the action of such persons.